Hemobilia after 49-days Accidental Hepatic Trauma and Twice Perihepatic Packing - Dedy Gunawanjati Sudrajat; Gunawanjati Sudrajat; Ellen Susanti; Sumaryono Sumaryono; Ari Fahrial Syam; Abdul Aziz Rani (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2009)
Hemobilia occurs in only 1.2–5% of patients with accidental liver trauma. Clinical presentation of hemobilia include one symptom and two signs known as the classic Quinke triad, upper abdominal pain, upper gastrointestinal bleeding and jaundice. This report describes a case of patient with hemobilia that had been diagnosed 49 days after accidental hepatic trauma and twice perihepatic packing. A 29-year old man with hematemesis melena came to the hospital with the history of hepatic accidental trauma and had already received twice perihepatic packing treatment. At first, the esophagogastroduodenoscopy could only find gastritis and duodenal ulcer. Subsesquently, the ultrasonography revealed liver hematoma. Diagnosis of hemobilia was made when bleeding exiting from the ampulla of Vater which then was confirmed by the second esophagogastroduodenoscopy. Surgery had been planned but the patient and his family had refused the procedure. Hemobilia should be considered in patients presenting with gastrointestinal blood loss after liver injury. The diagnosis is confirmed by esophagogastroduodenoscopy and angiography. Modalities used to stop bleeding include angiography with embolization, surgical intervention, observation, and electro- coagulation or photocoagulation.   Keywords: hematemesis, melena, liver injury, hemobilia, esophagogastroduodenoscopy